Value to Whom? The Patient Voice in the Value Discussion - Perfetto, Eleanor M.; Oehrlein, Elisabeth M.; Boutin, Marc; Reid, Sarah; Gascho, Eric (Value in health, 2017)
Professional societies and other organizations have recently taken a visible role trying to define treatment value via value frameworks and assessments, providing payer or provider recommendations, and potentially impacting patient access. Patient perspectives routinely differ from those of other stakeholders. Yet, it is not always apparent that patients were engaged in value framework development or assessment. To describe the development and content of the National Health Council’s (NHC’s) Rubric, a tool that includes criteria for evaluation of value frameworks specifically with regard to patient-centeredness and meaningful patient engagement. The NHC held a multistakeholder, invitational roundtable in Washington, DC, in 2016. Participants reviewed existing patient-engagement rubrics, discussed experiences with value frameworks, debated and thematically grouped hallmark patient-centeredness characteristics, and developed illustrative examples of the characteristics. These materials were organized into the rubric, and subsequently vetted via multistakeholder peer review. The resulting rubric describes six domains of patient-centered value frameworks: partnership, transparency, inclusiveness, diversity, outcomes, and data sources. Each domain includes specific examples illustrating how patient engagement and patient-centeredness can be operationalized in value framework processes. The NHC multistakeholder roundtable’s recommendations are captured in the NHC’s Rubric to assess value framework and model patient-centeredness and patient engagement. The Rubric is a tool that will be refined over time on the basis of feedback from patient, patient group, framework developer, and other stakeholder-use experiences.